A Centralized Outbreak of Varicella among Children Attending Preschool in Suzhou, China. (5th May 2020) - Zhang, Min; Gui, Guo-Ping; Guo, Feng; Fan, Xin-Fang; Zha, Ri-Sheng
Abstract : Background . Varicella vaccine is available for voluntary purchase with a single dose currently recommended for children aged ≥12 months. An epidemiological study was undertaken in order to determine the characteristics of the outbreak, assess vaccine effectiveness, and examine risk factors for vaccine failure. Methods . A varicella case was defined as a generalized papulovesicular rash (without other apparent causes) in a child without prior varicella attending the kindergarten during February 22 to April 7 of 2016. Varicella among vaccinated children (breakthrough varicella) was defined as varicella occurring >42 days after vaccination. Children's vaccination status was verified with immunization records through local vaccination information platform. Results . Of the 738 children, 664 (90.0%) had no prior varicella history. Of these, 364 (54.8%) had received a single-dose varicella vaccine before outbreak. A total of 30 cases occurred in the outbreak, and 9 of them (30%) had breakthrough varicella. Age at vaccination (<15 months vs. ≥15 months) and time since vaccination before the outbreak (<3 years vs. ≥3 years) were not related to the occurrence of breakthrough varicella (P > 0.05 ). Single-dose varicella vaccination was 64.7% effective in preventing any varicella. Conclusions . Single-dose varicella vaccine is effective in reducing the varicella attack rate, but not high enough to prevent outbreak. Timely detection and effective isolation are key factors in controlling varicella. Improving single-dose vaccination coverage and implementing two-dose vaccination strategy should be recommended to provide excellent protection to prevent varicella in the future in Suzhou.